Structure and cytotoxic activity relationship of curcumin derivatives on Myeloma cells - Supardjan Amir Margono; Muhammad Da’i (Indonesian Journal of Pharmacy, 2005)
Curcumin is a compound having broad spectrum of biological activities for example as anti-cancer. The aim of this research is to evaluate the relationship of structure and the cytotoxicity effect of curcumin and its derivatives on myeloma cell line. Some alkyl curcumin derivatives have beensynthesized and evaluated for the activity on myeloma cell lines with direct counting method. The IC50 values for curcumin, 4-methyl, 4-ethyl, 4-propyl, 4-isopropyl,4-benzyl, 4-phenyl dan 4-paramethylphenylcurcumin are 8.78, 3.45, 2.93, 2.18, 4.20, 3.87, >100, >100 μM respectively. Its seem that the activity of the curcumin derivatives is corelated to the stabilization of β diketone moiety and positive partial charge of those compound.Key words: Curcumin, myeloma cells, Curcumin derivatives